Impact of off‐label use regulations on patient care in dermatology – a prospective study of cost‐coverage applications filed by tertiary dermatology clinics throughout Germany. (7th July 2022) - Werner, R.N.; Pennitz, A.; Eisert, L.; Schmidle, P.; Zink, A.; Abraham, S.; Schäkel, K.; Wolff, I.; Goebeler, M.; Plange, J.; Sollfrank, L.; Zielbauer, S.; et al.
Abstract: Background: In dermatology, a medical speciality with a relatively high number of rare diseases, physicians often have to resort to off‐label treatment options. To avoid claims, physicians in Germany can file a cost‐coverage request (off‐label application, OL‐A). Objectives: Our aim was to investigate the extent to which the current regulations affect patient care. Material and methods: Prospective cohort study among tertiary dermatology clinics throughout Germany, consecutively including OL‐As (05/2019–09/2020) and assessing the follow‐up correspondence. We modelled regressions to assess factors associated with cost‐coverage decisions and the time needed by health insurers to process the OL‐As. Results: Thirteen clinics provided data on 121 OL‐As, two of which applied for on‐label treatments. Of the remaining 119 OL‐As, 70 (58.8%) were immediately approved and 44 (37.0%) rejected. Including cases with one or more appeals, 87 of 119 OL‐As (73.1%) were finally approved and 26 (21.9%) rejected. There was an association of the final approval rate with (1) the class of medication/treatment, with approval rates being significantly lower for JAK inhibitors than for biologics (OR 0.16, 95%‐CI: 0.03–0.82); (2) German state, with approval rates being lower in eastern than in western states (OR 0.30, 95%‐CI 0.12–0.76); and (3) cost of the intervention (no linear trend). However, none of these predictors was significant in our multiple logistic regression models. The median health insurer's processing time (first response) was 29 days (IQR 22–38). Our analyses showed no evidence of an association with the predictors we assessed. In cases approved, the median time from the decision to file an OL‐A to the actual initiation of the treatment was 65.5 days (IQR 51–92). Conclusions: Our study points to substantial delays and inequalities in the provision of timely health care for dermatological patients with rare diseases, often involving treatments for which there is no adequate approved therapy.